1990
DOI: 10.1001/archotol.1990.01870060058010
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of Methylprednisolone in Acute Vestibular Vertigo

Abstract: To assess the efficacy of corticosteroids in acute vestibular vertigo, we randomly selected 20 patients so that half took methylprednisolone and half took placebo. Extensive neurotologic examination confirmed the diagnosis. If no significant reduction of vertigo occurred within the first 24 hours of treatment, patients were instructed to switch medications. Patients were followed up prospectively for 1 month. Of the 10 patients receiving methylprednisolone, 9 had a marked reduction of vertiginous symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 21 publications
2
83
0
5
Order By: Relevance
“…This study confirms prior reports showing peripheral vestibular function improvement in patients with AUV receiving glucocorticoids on admission [3,20,21]. Additionally, we have shown that the improvement in canal paresis with glucocorticoid treatment correlates with a reduction in the degree of nystagmus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study confirms prior reports showing peripheral vestibular function improvement in patients with AUV receiving glucocorticoids on admission [3,20,21]. Additionally, we have shown that the improvement in canal paresis with glucocorticoid treatment correlates with a reduction in the degree of nystagmus.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies hinted that glucocorticoids may not be clinically beneficial in AUV [10], despite apparent improvement in vestibular function [3,15,17,20]. Indeed, both a systematic review [13] and later a Cochrane review of four trials found no significant difference between corticosteroid and placebo in the symptomatic recovery of vestibular function [11], but only one study had assessed symptom recovery [20], and this was not a primary study outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Such an analysis is particularly important in the light of recent suggestions that steroid treatment for acute VN improves peripheral-vestibular recovery (albeit measured with the caloric test and without symptom assessment) [1,16].…”
Section: Discussionmentioning
confidence: 99%
“…As part of the NHAMCS protocol, trained hospital staff members gather data from ED visit records during a randomly assigned 4-week data period for each Canalith-repositioning maneuvers Proven benefit 25,26 and recommended 14,15,27 Not indicated Corticosteroids Not indicated Proven benefit [28][29][30] and recommended 31,32 Vestibular sedatives Ineffective 14,15,33,34 and potentially harmful from exacerbation of balance disturbance 5,13,15 or delay in repositioning maneuvers 5,15,35 Standard treatment 8,17,20,32,36 APV = acute peripheral vestibulopathy; BPPV = benign paroxysmal positional vertigo.…”
Section: Study Protocolmentioning
confidence: 99%